Negative learning bias is associated with risk aversion in a genetic animal model of depression - Shabel, Steven J.; Murphy, Ryan; Malinow, Roberto (Frontiers in Human Neuroscience, 2014)
The lateral habenula (LHb) is activated by aversive stimuli and the omission of reward, inhibited by rewarding stimuli and is hyperactive in helpless rats – an animal model of depression. Here we test the hypothesis that congenital learned helpless (cLH) rats are more sensitive to decreases in reward size and/or less sensitive to increases in reward than wild-type (WT) control rats. Consistent with the hypothesis, we found that cLH rats were slower to switch preference between two responses after a small upshift in reward size on one of the responses but faster to switch their preference after a small downshift in reward size. cLH rats were also more risk-averse than WT rats – they chose a response delivering a constant amount of reward (“safe” response) more often than a response delivering a variable amount of reward (“risky” response) compared to WT rats. Interestingly, the level of bias towards negative events was associated with the rat’s level of risk aversion when compared across individual rats. cLH rats also showed impaired appetitive Pavlovian conditioning but more accurate responding in a two-choice sensory discrimination task. These results are consistent with a negative learning bias and risk aversion in cLH rats, suggesting abnormal processing of rewarding and aversive events in the LHb of cLH rats.